2021
DOI: 10.3390/nano11030582
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Stable Ionic Liquid-Based Nanofluids into Polymer Membranes. Part II: Gas Separation Properties toward Fluorinated Greenhouse Gases

Abstract: Membrane technology can play a very influential role in the separation of the constituents of HFC refrigerant gas mixtures, which usually exhibit azeotropic or near-azeotropic behavior, with the goal of promoting the reuse of value-added compounds in the manufacture of new low-global warming potential (GWP) refrigerant mixtures that abide by the current F-gases regulations. In this context, the selective recovery of difluorometane (R32, GWP = 677) from the commercial blend R410A (GWP = 1924), an equimass mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
(83 reference statements)
0
24
0
Order By: Relevance
“…Constantino et al [236] presented pervaporation data for multicomponent mixtures in the absence of reaction for the compounds involved in the esterification of acrylic acid with n-butanol at different temperatures. This experimental data is very useful for designing and optimising pervaporation-based hybrid processes for butyl acrylate synthesis [213].…”
Section: Membranes For Pervaporationmentioning
confidence: 99%
See 3 more Smart Citations
“…Constantino et al [236] presented pervaporation data for multicomponent mixtures in the absence of reaction for the compounds involved in the esterification of acrylic acid with n-butanol at different temperatures. This experimental data is very useful for designing and optimising pervaporation-based hybrid processes for butyl acrylate synthesis [213].…”
Section: Membranes For Pervaporationmentioning
confidence: 99%
“…Remarkable CO 2 solubility and tunability are essential features of this unique platform. The potential of ionic liquid materials to improve membranebased CO 2 separation processes has been demonstrated, either through the preparation of supported ionic liquid membranes (SILMs) [45,[187][188][189][190][191][192][193][194][195][196][197][198], the blending of ionic liquids with poly(ionic liquid)s [199][200][201][202][203][204][205][206][207][208] or, more recently, through the development of mixed matrix membranes [209][210][211][212][213][214].…”
Section: Membranes For Gas Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the CILPM based on [C 2 C 1 Im][BF 4 ] showed higher permeability towards the HFCs R-32 and R-134a compared to the HFO R-1234yf, demonstrating to be useful for the separation of HFC/HFO blends [112]. Furthermore, Pebax membranes were functionalized with the so-called ioNanofluids, a suspension of exfoliated graphene nanoplatelets in the FIL [C 2 C 1 py][C 4 F 9 SO 3 ], and used for the separation of the R-410A refrigerant, showing enhanced gas permeation relative to the neat membranes [113].…”
Section: Gas Separation Processes Using Fluorinated Ionic Liquids-bas...mentioning
confidence: 99%